Efficient Interfacial Solar Steam Generator with Controlled Macromorphology Derived from Flour via "Dough Figurine" Technology. Issue 9 (1st September 2019) - Li, Zhengtong; Wang, Chengbing; Li, Zeyu; Deng, Lin; Su, Jinbu; Shi, Jing; An, Meng
Abstract : A shape‐ and size‐controlled, low‐cost, eco‐friendly solar‐absorber material is urgently desired for solar‐driven interface steam generators (SISGs), where the macro‐shape plays an important role in energy regulation. A facile, sustainable, and scalable approach is proposed to produce tailored SISGs with controlled macromorphology derived from flour via "dough figurine" technology. More details can be found in article number1900406 by Chengbing Wang, Meng An, and co‐workers.